Cancer screening participation in schizophrenic outpatients and the influence of their functional disability on the screening rate: A cross‐sectional study in Japan. Issue 12 (5th September 2017) - Fujiwara, Masaki; Inagaki, Masatoshi; Nakaya, Naoki; Fujimori, Maiko; Higuchi, Yuji; Hayashibara, Chinatsu; So, Ryuhei; Kakeda, Kyoko; Kodama, Masafumi; Uchitomi, Yosuke; Yamada, Norihito
Abstract : Aim: The influence of schizophrenic patients' functional disability on cancer screening participation worldwide is unclear. There are few findings on the disparities in schizophrenic patients' participation in cancer screening programs in Asia. The aim of this study was to investigate the screening rate and the associations between screening and symptom severity/functional disability in patients with schizophrenia. Methods: This cross‐sectional study was conducted in a psychiatric hospital outpatient clinic in Japan. We recruited schizophrenic patients meeting the national program criteria for cancer screening for colorectal, gastric, lung, breast, and cervical cancer ( n = 224, 223, 224, 110, and 175, respectively). Receipt of cancer screenings was assessed using a self‐report questionnaire. Scores on the modified Global Assessment of Functioning (mGAF) were evaluated by participants' primary psychiatrists. Results: Rates of cancer screenings were as follows: 24.1% for colorectal, 21.5% for gastric, 30.8% for lung, 25.5% for breast, and 19.4% for cervical cancer. A multivariable logistic analysis showed that a 1‐point increase in severity/disability (100 minus mGAF score) was associated with significantly lower odds ratios (OR) for receipt of cancer screenings, except for breast cancer (OR, 0.95, 95% confidence interval [CI], 0.93–0.98 for colorectal; OR, 0.96, 95%CI, 0.93–0.98 for gastric; OR, 0.95, 95%CI, 0.93–0.97 for lung; OR, 0.97, 95%CI, 0.94–1.00 for breast; and OR, 0.95, 95%CI, 0.92–0.98 for cervical cancer). Conclusion: The findings demonstrated low rates of cancer screenings in schizophrenic patients in Japan. Our study suggests the need to encourage attendance at cancer screenings, especially in schizophrenic patients with severe symptoms/functional disability.